THE USING OF DIFFERENT EXTRACTIONTIME ON THE ANTIOXIDANT ACTIVITY OF SEA CUCUMBER (Holothuria atra) - Nadia Adilla; Mery Sukmiwati; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was aimed to determine the effect of different extraction time on the antioxidant activity of sea cucumber (Holothuria atra). The method used was an experimental method, with Completely Randomized Design (CRD) consisting of 3 treatment levels T3 (maceration for 72 hours), T4 (maceration for 96 hours) and T5 (maceration for 120 hours). The series of research activities were divided into 2 stages: 1) Preparation of raw materials of sea cucumber (Holothuria atra), 2) Extraction with maceration of sea cucumber flour. The parameters tested included yield, chemical content (proximate analsis), secondary metabolites (phytochemical analysis) and antioxidant activity of sea cucumber concentrate. The chemical content of meat and skinof sea cucumber includes water 7.35 % (WW), ash 19.20 % (DW), and protein 74.82 %( DW), fat 2.64 % (DW) and carbohydrate 3.34 % (DW). The results showed that the secondary metabolites on sea cucumber include steroids, alkaloids, saponins and phenolics. The different extraction times had a very significant effect on the antioxidant activity of sea cucumber, with IC50 values as follows: T3(1589.6423 mg/L), T4(902.8443 mg/L) and T5 (449.9066mg/L). IC50 values showed that the antioxidant activity of sea cucumber concentrate was weak in T5 time treatment (120 hours) and very weak in the treatment of T3 (72 hours) and T4 (96 hours) time. Keywords:antioxidants, extraction, sea cucumber,secondary metabolites